Suppression of the root-knot nematode disease through background fertilization with organic amendments - Lillo, Paula; Sánchez-Moreno, Sara; Vela, Maria Dolores; de Cara-García, Miguel; Talavera, Miguel (Frontiers in Plant Science, 2025)
IntroductionOrganic amendments like manures, sludges, and composts have significant potential to enhance soil’s physical, chemical, and microbiological conditions, aiding in the restoration of soils disturbed by intensive agricultural practices and compensating for losses due to plant pathogens. This study investigates the effects of background fertilization with organic amendments and inorganic fertilizers on the root-knot nematode (RKN) disease in cucumber and the functioning of the soil ecosystem.MethodsField trials were conducted in a greenhouse infested with Meloidogyne incognita, applying six background fertilization treatments: fresh cow manure, composted cow manure, fresh chicken manure, pelletized chicken manure, slow-release inorganic fertilizer, and fast-release inorganic fertilizer. Each amendment was adjusted to provide equivalent units of N-fertilization. After 120-day crop cycles, total fruit production and RKN-disease severity were evaluated, along with nematode-based indices.ResultsThe fresh chicken manure treatment yielded the highest cucumber production, despite no significant differences in RKN-disease severity between treatments. Different organic amendments influenced RKN mortality at transplanting, with fresh chicken manure being the most effective in reducing RKN abundances in soil, followed by pelletized chicken manure, fresh cow manure, and composted cow manure. The inorganic fertilizers were the least effective in reducing RKN soil abundances. Organic amendments increased the complexity of the soil food web, whereas fast-release inorganic fertilizers led to its degradation and simplification. Cucumber cultivation and fertigation throughout the crop cycle enriched the soil with nutrients, intensified the bacteria-dominated organic matter degradation channel, and further simplified the soil food web.DiscussionThis study demonstrates the potential of organic amendments to enhance soil health and partially suppress root-knot nematode disease in cucumber.